Fix it with food : every meal easy - Symon, Michael, 1969-; Trattner, Douglas (Clarkson Potter/Publishers, 2021)
"125 simple, delicious recipes for breakfast, lunch, and dinner to help you manage autoimmune issues all day-plus an all-new 10-day, 30-recipe reset to identify your food triggers-from the New York Times bestselling author of Fix It with Food. During the first few months of 2020, Michael Symon religiously posted "Symon Dinners" on Instagram every day to help his fans keep pantry-inspired meals fun and varied. The response was so great and his followership so engaged that creating a cookbook of simple weekday breakfasts, lunches, and dinners became a priority for him. In Fix It with Food: Every Meal Easy, Michael combines simple dishes for busy weekdays and meals that address autoimmune triggers for a collection of 125 health-supportive recipes. The chapters are divided by what trigger you're avoiding, including No Meat, No Dairy, and No Flour. If you're not sure what your food triggers are, the ten-day reset will help you figure out which foods to avoid. After the reset, Michael offers guidance about how to reintegrate foods into your routine. Through fan feedback, Michael discovered that most people using his first book didn't need four servings-most wanted just enough for two meals, so in Every Meal Easy, all of the main recipes yield two meals or enough for one meal plus leftovers. And since sometimes you have a crowd to cook for, Michael offers helpful information regarding how to double recipes when needed. Readers will also find a list of his favorite 30 anti-inflammatory friendly ingredients to keep on hand all the time and a master ingredient substitution list, so if you don't have kale or black beans on hand, you can swap in whatever you have in your fridge or pantry. With Michael's encouraging voice and flexible recipes, Fix It with Food: Every Meal Easy is a must-have for anyone who is looking to feel better without compromising eating well"--